Nanostructured WO3·xH2O deposition effects on the antimicrobial activities of nano TiO2-coated bamboo. (October 2022) - Ma, Rumin; Chen, Yuhe; Wu, Zaixing; Bao, Minzhen; Xiao, Zizhang; Sun, Fengbo; Li, Jingpeng
Abstract: Antibacterial and antifungal activities of nanostructured WO3 · x H2 O ( x = 0.33 or 1) decorated TiO2 films on bamboo surfaces were evaluated for the first time. Anatase TiO2 films were easily loaded on the surface of bamboo (TB) by a hydrothermal method. Nanostructured WO3 · x H2 O ( x = 1 or 0.33) with different crystal phases were respectively synthesized on TB by adding (O-WTB) or not adding (WTB) oxalic acid employing a hydrothermal method. Both O-WTB and WTB demonstrated obvious synergistic antibacterial abilities against Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ) and good outdoor antifungal ability of 60-day experiment. The electron paramagnetic resonance (EPR) spectra of O2 ˉ and OH radicals showed that the antifungal activity of O-WTB and WTB was due to their good photocatalytic activity and synergistic antifungal effect with hybrid structure, respectively. Nanostructured WO3 · x H2 O with different crystal phases displayed differentiated antimicrobial activities and can be employed as potential antimicrobial agents. Highlights: Antimicrobial activities of WO3 · x H2 O decorated TiO2 films on bamboo were evaluated. WO3 · x H2 O with different crystal phases were synthesized by adding oxalic acid. WO3 · x H2 O decorated TiO2 films showed obvious synergistic antibacterial abilities. Composite films presented good outdoor antifungal ability of 60-day experiment.